2010
DOI: 10.1136/tc.2010.037093
|View full text |Cite
|
Sign up to set email alerts
|

Individual-level factors associated with intentions to quit smoking among adult smokers in six cities of China: findings from the ITC China Survey

Abstract: BackgroundOver 350 million smokers live in China, and this represents nearly one-third of the smoking population of the world. Smoking cessation is critically needed to help reduce the harms and burden caused by smoking-related diseases. It is therefore important to identify the determinants of quitting and of quit intentions among smokers in China. Such knowledge would have potential to guide future tobacco control policies and programs that could increase quit rates in China.ObjectiveTo identify the correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
83
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 51 publications
26
83
2
Order By: Relevance
“…This finding could explain the observation that low education levels could be a barrier for smoking cessation (Breslau and Peterson, 1996;Khuder et al, 1999), although the causal relationship should be confirmed in further prospective research. Consistent with a recent study that showed that lower intention to quit smoking was associated with higher nicotine dependence (Feng et al, 2010), our study found that willingness to quit smoking was inversely correlated with FTND scores and urinary cotinine levels, respectively. This finding could further support our study hypothesis that urinary cotinine levels reflect nicotine dependence status in active smokers because increased intention to quit smoking often leads to a substantial increase of smoking cessation attempts.…”
Section: Discussionsupporting
confidence: 92%
“…This finding could explain the observation that low education levels could be a barrier for smoking cessation (Breslau and Peterson, 1996;Khuder et al, 1999), although the causal relationship should be confirmed in further prospective research. Consistent with a recent study that showed that lower intention to quit smoking was associated with higher nicotine dependence (Feng et al, 2010), our study found that willingness to quit smoking was inversely correlated with FTND scores and urinary cotinine levels, respectively. This finding could further support our study hypothesis that urinary cotinine levels reflect nicotine dependence status in active smokers because increased intention to quit smoking often leads to a substantial increase of smoking cessation attempts.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, among smokers, the more number of cigarettes smoke per day, the lower the willingness to quit (Hyland et al, 2004;Hyland et al, 2006;Fagan et al, 2007;Feng et al, 2010). Our study found the similar results as smokers who smoke 15 cigarettes or more per day had the odds of developing intention to quit 0.4 times lower than those who smoke less than 5 cigarettes per day.…”
Section: Discussionsupporting
confidence: 78%
“…Along with the effort to avoid the PHWs (avoidance), previous attempt to quit smoking, level of worrying about health consequences and always read the PHWs were also associated with intention to quit. The association between those factors and intention to quit has also been observed in other studies (Hammond et al, 2003;Borland R et al, 2009a;Borland R et al, 2009b;Feng et al, 2010;Panda et al, 2014). A smoker who attempted to quit in the past but failed may obtain new motivation from the PHWs and want to try again.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies have noted that smokingrelated behaviour, history, and opinions are the most robust predictors of cessation intentions (33). This study was unable to examine potential differences between those attempting to quit and those who had recently quit, due in part to the small sample size of recent quitters surveyed (n = 38).…”
Section: Resource Utilizationmentioning
confidence: 65%
“…In a study of Hong Kong Chinese, over 50% of daily smokers reported a desire to quit (32), while further studies have suggested that smoking behaviour (e.g. heaviness of smoking, past quit attempts, overall opinion of smoking) remains the most critical predictor of quit attempts (33).…”
Section: Introductionmentioning
confidence: 99%